2011
DOI: 10.2147/ndt.s18455
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of insulin resistance in narcoleptic patients: dependent or independent of body mass index?

Abstract: Background:Narcolepsy is a severe sleep-wake cycle disorder resulting in most cases from a lack of orexin, the energy balance-regulating hormone. Narcoleptic patients have been reported to suffer from an excess morbidity of Type 2 diabetes, even after correction for their often elevated body mass index.Methods:To explore whether narcolepsy is specifically associated with a propensity to develop insulin resistance, we measured fasting glucose, insulin, and intact proinsulin levels in 43 narcoleptic patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…We did not find any significant differences between patients with narcolepsy and controls according to standard measurements of the OGTT. These results are in line with OGTT data from Beitinger et al (2012) and data on insulin sensitivity from Engel et al (2011), suggesting that narcolepsy is not directly associated with disturbances of glucose metabolism. In these studies and in ours, patients with narcolepsy and controls were matched for BMI.…”
Section: Discussionsupporting
confidence: 88%
“…We did not find any significant differences between patients with narcolepsy and controls according to standard measurements of the OGTT. These results are in line with OGTT data from Beitinger et al (2012) and data on insulin sensitivity from Engel et al (2011), suggesting that narcolepsy is not directly associated with disturbances of glucose metabolism. In these studies and in ours, patients with narcolepsy and controls were matched for BMI.…”
Section: Discussionsupporting
confidence: 88%
“…As treated and untreated patients had similar BMI, it was hypothesized that elevated BMI resulted from the pathophysiology of narcolepsy itself (e.g., loss of orexin peptide) or disease behavior such as reduced physical activity. More recently, blood glucose regulation and T2D was investigated in two studies of patients with narcolepsy using BMI matched controls (71, 72). Findings from both of these studies showed that narcoleptic patients did not have elevated risk of developing T2D or blood glucose dysregulation independent of BMI.…”
Section: Narcolepsymentioning
confidence: 99%
“…Honda et al found that narcolepsy was associated with increased frequency of type 2 diabetes [70]. However, subsequent studies have failed to find evidence that narcolepsy increases the risk of insulin resistance or glucose intolerance (and consequently of type 2 diabetes) independently of BMI [71 72]. …”
Section: Introductionmentioning
confidence: 99%